Detection of Pest Feeding Traces on Industrial Wood Surfaces with 3D Imaging - Andrzej Sioma; Keiko Nagashima; Bartosz Lenty; Arkadiusz Hebda; Yasutaka Nakata; Kiichi Harada (Applied Sciences)
This paper presents a method for detecting holes and grooves made by wood-boring pests. As part of the production process automation, wood delivered from sawmills is checked for defects visible on its surface. One of the critical defects that disqualifies wood from further processing is the presence of feeding marks left by various types of pests on its surface. This paper proposes a method for detecting this type of damage based on analysis of three-dimensional images of the wood surface. Three-dimensional imaging methods and the image resolutions resulting from the adopted imaging system’s configurations are discussed. An analysis of the advantages and disadvantages of the methods investigated is presented, together with an assessment of their potential use in the implementation of the assigned control task, i.e., the detection of holes and grooves made by pests. Three-dimensional image parameters and interferences affecting the quality of the recorded image are described, along with the designed algorithm for identifying holes and grooves and the parametric description of the identified defect. The imaging effects for selected surfaces bearing signs of pest damage and the parameters describing the effectiveness of the present industrial solution are also presented. This paper demonstrates that it is possible to build a three-dimensional image to identify damage effectively within a minimum diameter of 1mm. It makes it possible to observe the damage carried out by most wood-boring pests.